Self-healing hydrogel constructed based on carbon dot crosslinking as well as preparation method and application of self-healing hydrogel

By crosslinking the carbon dots containing active carbonyl groups with amine-containing organic polymer compounds in aqueous solution, a self-healing hydrogel with a porous structure was prepared, which solved the problem of high cost and low yield of self-healing hydrogels in the prior art, achieved an efficient and low cost preparation process, and gave it excellent antibacterial and wound-promoting healing ability.

CN119529319APending Publication Date: 2025-02-28THE THIRD XIANGYA HOSPITAL OF CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411702869.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing methods for synthesizing self-healing hydrogels based on organic or natural polymer materials have high cost and low yields, and the polymer materials in nanomaterials only play a load role in the hydrogel system, which limits its large-scale commercial application.

Method used

A self-healing hydrogel with a porous structure was prepared by mixing the carbon dots containing active carbonyl groups with an amine group in an aqueous solution system and cross-linking reaction. This method is simple in process, low in cost, and has a large output.

Benefits of technology

The prepared self-healing hydrogel not only has excellent antibacterial effects and wound-promoting healing ability, but also shows good sustained release effects, which are suitable for applications in the fields of tissue engineering, regenerative medicine and cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529319A_ABST
    Figure CN119529319A_ABST
Patent Text Reader

Abstract

The invention relates to hydrogel constructed based on carbon dot crosslinking and a preparation method and application thereof, and the preparation method comprises the following steps: mixing active carbonyl-containing carbon dots and an amino-containing organic high-molecular compound in an aqueous solution system, and carrying out a crosslinking reaction to obtain self-healing hydrogel; the preparation method disclosed by the invention is simple in process, short in period and high in yield, the production cost of the self-healing hydrogel is greatly reduced, and industrial production is facilitated; the prepared self-healing hydrogel can be well applied to the fields of medicines and cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and more specifically, to a self-healing hydrogel based on carbon dot cross-linking, and a preparation method and application thereof. Background Art

[0002] Carbon dots (CDs) can be generally defined as zero-dimensional carbon-based nanomaterials with a size less than 10 nm, because they have a variety of physicochemical properties and favorable attributes, such as excellent biocompatibility and unique optical properties. Carbon dots are widely used in the biomedical field, such as bioimaging, phototherapy, drug / gene delivery, antibacterial and antioxidant nanomedicine.

[0003] Hydrogel is a biomaterial that can combine with a large amount of water to form a gel matrix. Due to its three-dimensional hydrophilic polymer cross-linked network, it is often used as an ideal therapeutic agent for drug delivery systems. Among them, self-healing hydrogels have dynamic cross-linking between networks and can be restored to their original state through self-repair after being destroyed. Its function in the biomedical field has attracted widespread interest from researchers. However, the current methods for synthesizing self-healing hydrogels based on organic or natural polymer materials almost all require modification of organic or natural polymer materials, which undoubtedly increases the synthesis cost of self-healing hydrogels and limits their production. In recent years, self-healing hydrogels constructed by loading various nanomaterials including carbon dots have integrated the functions of nanomaterials and macromolecules, significantly enriching their applications. However, these various nanomaterials including carbon dots have the disadvantages of complex synthesis process, high cost and low production, and the polymer substances in the hydrogel system often only play the role of loading nanomaterials. These factors limit their application in large-scale commercialization. Therefore, there is an urgent need to prepare self-healing hydrogels on a large scale based on cheaper, easier to synthesize and larger-yield functional CDs and chemically cross-link such CDs with other organic polymers under simple reaction conditions. Summary of the invention

[0004] Based on the above technical problems existing in the prior art, the present invention provides a method for preparing a hydrogel based on carbon dot cross-linking construction. The self-healing hydrogel prepared by this method can have an excellent antibacterial effect, and has low cost, simple synthesis process and high yield.

[0005] In order to achieve the above object, the technical solution of the present invention is as follows:

[0006] A method for preparing a self-healing hydrogel based on carbon dot cross-linking construction comprises the following steps:

[0007] In an aqueous solution system, carbon dots containing active carbonyl groups and organic polymer compounds containing amine groups are mixed and then subjected to cross-linking reaction to obtain a self-healing hydrogel.

[0008] In some embodiments, the reaction temperature is 25-55°C.

[0009] In some embodiments, in the aqueous solution, the concentration of carbon dots is 0.5-10 wt %; and the concentration of the organic polymer compound is 1-20 wt %.

[0010] In some embodiments, the mass ratio of the carbon dots to the organic polymer compound is (1:40)-(10:1).

[0011] In some embodiments, the organic polymer compound includes at least one of chitosan and its derivatives, chitosan oligosaccharides and their derivatives, polyacrylamide and its derivatives, gelatin and its derivatives, polyethyleneimine and its derivatives, polylysine and its derivatives, polyacrylamide and its derivatives, gelatin and its derivatives, polyethyleneimine and its derivatives, and silk fibroin and its derivatives.

[0012] In some embodiments, the preparation method comprises the following steps:

[0013] Active carbonyl-containing carbon dots are prepared using aldehyde compounds and / or ketone compounds as substrates, and then the active carbonyl-containing carbon dots and amine-containing organic polymer compounds are mixed in an aqueous solution system and subjected to cross-linking reaction to obtain a self-healing hydrogel.

[0014] In some embodiments, the method for preparing the carbon dots containing active carbonyl groups comprises the following steps:

[0015] Slowly add an alkaline substance to a solution containing aldehyde compounds and / or ketone compounds, and stir the solution for reaction for more than 30 minutes at room temperature. After the reaction is completed, ultrasonically treat the obtained reaction product with dilute acid and water until solid precipitates, then separate the solid from the liquid, wash the solid with water until it is neutral, and dry it to obtain the carbon dots containing active carbonyl groups.

[0016] In some embodiments, the aldehyde compound is at least one of acetaldehyde, propionaldehyde, butyraldehyde, succinaldehyde, valeraldehyde, glutaraldehyde, hexanal, adipaldehyde, heptaldehyde, octanal, nonanal, decanal, undecanal, dodecanal, tridecanal, tetradecanal, pentadecaldehyde, phenylacetaldehyde, and methylphenylacetaldehyde.

[0017] In some embodiments, the ketone compound is at least one of acetone, 2-butanone, 2-pentanone, 3-pentanone, 2-hexanone, cyclohexanone, 2-heptanone, cycloheptanone, 2-octanone, cyclooctanone, 2-nonanone, decanone, undecanone, dodecanone, tridecanone, tetradecanone, pentadecone, acetophenone, and methylacetophenone.

[0018] In some embodiments, the alkaline substance is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, carbonate, and carboxylate.

[0019] In some embodiments, the preparation of the carbon dots further includes the step of adding a doping element source to the aldehyde-containing compound and / or ketone-containing compound; specifically, the doping element source includes but is not limited to various natural or synthetic small molecules containing at least one of B, N, Si, P, S and halogen elements.

[0020] The present invention also provides a self-healing hydrogel obtained by the method of any of the above embodiments.

[0021] The present invention also provides the use of the self-healing hydrogel in the fields of applied tissue engineering, regenerative medicine and cosmetics.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention utilizes the active carbonyl groups on the carbon dots to react with the amine groups on the organic polymer compounds to form Schiff chemical bonds, and the surface functional groups of the carbon dots and the functional groups of the organic polymer compounds to cross-link to form intermolecular hydrogen bonds to prepare a self-healing hydrogel with a porous structure. The self-healing hydrogel has excellent antioxidant properties, broad-spectrum antibacterial properties and good wound healing promoting ability, and also has a good sustained-release effect.

[0024] The self-healing hydrogel synthesis process of the invention has simple technology, short cycle, large output and high yield, which greatly reduces the production cost of the self-healing hydrogel and is conducive to industrial production and application in the medical field. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a photo of the self-healing hydrogel of the present invention;

[0026] Figure 2 This is a scanning electron microscope image of the self-healing hydrogel of the present invention;

[0027] Figure 3 is an infrared spectrum of the self-healing hydrogel of the present invention;

[0028] Figure 4 This is a graph showing the antibacterial test results of the self-healing hydrogel of the present invention;

[0029] Figure 5 This is a diagram showing the experimental results of the self-healing hydrogel of the present invention in treating MRSA-infected diabetic mouse wounds;

[0030] Figure 6 This is an infrared spectrum of graphene quantum dots without active carbonyl groups used as a comparison in the present invention;

[0031] Figure 7These are photographs of the carboxymethyl chitosan solution, the graphene quantum dot solution without active carbonyl groups, and the solution after carboxymethyl chitosan and graphene quantum dots were mixed at room temperature for half an hour in the comparative example; wherein (A) is the carboxymethyl chitosan solution, (B) is the graphene quantum dot solution containing active carbonyl groups, and (C) is the solution after the two were mixed and stirred. DETAILED DESCRIPTION

[0032] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.

[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0034] Example 1

[0035] The preparation of active carbonyl carbon dots comprises the following steps:

[0036] Slowly (add within 1-3 minutes) add 12g of sodium hydroxide to 40mL of acetaldehyde solution, and continue stirring the reaction at room temperature for 2 hours. After the stirring is completed, the reaction product is ultrasonically treated with dilute hydrochloric acid and water until the reaction product containing active carbonyl carbon dots is precipitated, and then the product is washed with deionized water until it is neutral; finally, the active carbonyl carbon dots are dried in an oven at 70°C to obtain a solid powder containing active carbonyl carbon dots for use (the active carbonyl carbon dots can be prepared by scaling up in equal proportions).

[0037] Example 2

[0038] A preparation method of a self-healing hydrogel comprises the following steps:

[0039] First, weigh an appropriate amount of carboxymethyl chitosan and dissolve it in deionized water. After it is completely dissolved, add an equal volume of the aqueous solution containing active carbonyl carbon dots prepared in Example 1 (the final mass percentage of carboxymethyl chitosan in the mixed system in this embodiment is 4%, and the final mass percentage of active carbonyl carbon dots is 2%), and continue stirring at 25°C for 30 minutes to react. After gelation, the preparation of the hydrogel is completed.

[0040] like Figure 1As shown, Figure (A) is a photograph of a large-volume self-healing hydrogel prepared in a simple step in the laboratory (after being stirred into gel and placed at room temperature for 20 minutes). Figure (B) is a diagram of the verification results of the self-healing properties of the hydrogel: Figure B1 is a hydrogel sample after being cut in half, and Figure B2 is a picture of the two halves of the hydrogel after being placed at room temperature for 30 minutes along the cut edges; Figure B3 is a picture of the effect of the hydrogel sample in Figure B2 after being stretched on both sides. The results in Figure B show that the hydrogel prepared by the present invention has good self-healing properties. Figure B3 is a picture of the hydrogel sample after being stirred into gel and passing through a 2.5mL syringe needle. The results show that the hydrogel prepared by the present invention has good injectable properties.

[0041] Characterization of the microscopic morphology of the self-healing hydrogel: The prepared hydrogel was freeze-dried, and the freeze-dried sample was cut with a scalpel. The sample was sprayed with gold in a vacuum ion sputtering instrument with the cross section facing upward, and then observed and photographed using a SEM (test voltage was 5 keV).

[0042] like Figure 2 As shown, the microscopic morphology of the hydrogel of the present invention was characterized and analyzed using a scanning electron microscope (SEM), and the results showed that the hydrogel had a porous structure with relatively uniformly distributed pores of different sizes, very uniform pores, and very smooth pore walls. This can be attributed to the formation of an interwoven network between the active carbonyl-containing carbon dots and the carboxymethyl chitosan.

[0043] Infrared spectroscopic characterization of self-healing hydrogel: Appropriate amounts of carboxymethyl chitosan, active carbonyl carbon dots and freeze-dried hydrogel powder were weighed and ground evenly with dried potassium bromide powder in a mortar. After pressing, the samples were detected on an infrared spectrometer (wave number range: 4000-500 cm -1 ).

[0044] like Figure 3 As shown, Figure 3 The FTIR spectra of carboxymethyl chitosan (CMCS), active carbonyl carbon dots (CDs) and self-healing hydrogel (Hydrogel) are shown in Figure 2. The FTIR spectrum analysis shows that the active carbonyl carbon dots are located at 1716 cm -1 The aldehyde peak at 1587 cm-1 was almost eliminated in the self-healing hydrogel. This is because the aldehyde groups on the surface of the active carbonyl carbon dots reacted with the amine groups in the carboxymethyl chitosan to produce imine bonds. -1 The characteristic vibration peak of the imine bond at 3276 cm -1 The peaks at 3375 cm-1 and 3375 cm-2 are characteristic peaks of NH or OH, which are higher than those of carboxymethyl chitosan and carbon dots containing active carbonyl groups. -1 and 3431cm -1 The characteristic peak at 470 nm red-shifted, which proved the formation of intermolecular hydrogen bonds.

[0045] In vitro antibacterial experiment of self-healing hydrogel: The killing effect of hydrogel on three kinds of bacteria (Staphylococcus aureus, Escherichia coli and methicillin-resistant Staphylococcus aureus) was determined by agar plate counting method. 200 μL of PBS, carboxymethyl chitosan and hydrogel were added to a 48-well plate, and 20 μL of bacterial suspension (LB, 1.5×10 8 CFU / mL) was added to each group of sample wells. The culture plate was placed in a humidified box and then placed in an incubator at 37°C for 4 hours. After the mixed system after resuspending the bacterial suspension was diluted in an appropriate ratio, 100 μL was inoculated on the agar plate, spread evenly and placed in a constant temperature incubator (37°C), and the plate was inverted to prevent contamination. After 18 hours, the culture dish was photographed and the bacterial growth on each agar plate was recorded. Finally, the relative bacterial activity was calculated by counting the number of colonies.

[0046] like Figure 4 As shown, the self-healing hydrogel group has better antibacterial effects on the above three bacteria than the control group and the carboxymethyl chitosan group. Among them, the survival rates of Staphylococcus aureus, Escherichia coli and methicillin-resistant Staphylococcus aureus in the self-healing hydrogel group were 2.9%, 28.1% and 2.7%, respectively; the survival rates of the above three bacteria in the carboxymethyl chitosan group were 17.6%, 54.5% and 16.2%, respectively. Therefore, the self-healing hydrogel has a wide antibacterial spectrum, which is stronger than the antibacterial effect of simple carboxymethyl chitosan, and has a better antibacterial effect on Gram-positive bacteria.

[0047] Self-healing hydrogel for the treatment of MRSA-infected diabetic mouse wounds: Clean-grade 10-week-old male C57 mice were selected. After one week of adaptive feeding, STZ (100 mg / kg) solution was given twice by intraperitoneal injection. The diabetic mouse model was successfully established when the blood glucose concentration was stable and exceeded 16.7 mM. The experimental diabetic mice were anesthetized by inhalation of a mixture of nebulized isoflurane and oxygen. First, the back area of ​​the diabetic mice was prepared for skin preparation. After disinfection with 75% alcohol, a skin puncher and surgical scissors were used to remove a circular full-thickness skin with a diameter of about 10 mm to form a wound, and a rubber ring was fixed on the wound. After surgery, 50 μL of fresh MRSA bacterial suspension (bacterial density was 1×10 8CFU / mL). After 24 hours, the successfully infected diabetic mice were selected according to whether the wound surface was red, swollen, hot, and whether there was purulent exudate. The mice with successful modeling were randomly divided into a control group, a carboxymethyl chitosan (CMCS) group, a group containing active carbonyl carbon dots (CDs), and a self-healing hydrogel (Hydrogel) group. The wounds of the above four groups of mice were treated with equal volumes of PBS, 5% CMCS solution, 2% CDs solution, and Hydrogel, respectively. The wound healing was observed and photographed on days 0, 3, 7, 11, and 15 after surgery.

[0048] like Figure 5 As shown: Figure A shows the Control group, CMCS group, CDs group and Hydrogel group vertically, and the general picture of wound healing on days 0, 3, 7, 11 and 15 after surgery vertically. Figure B is an analysis of the wound healing rate of each group at different time points. The results showed that compared with the Control group, the CMCS group, CDs group and Hydrogel group all had the effect of promoting the healing of MRSA-infected diabetic wounds. On the 15th day after surgery, the wound healing rates of the CMCS group, CDs group and Hydrogel group were 78.3%, 84.4% and 93.6%, respectively, which were significantly higher than those of the Control group (68.5%), and the Hydrogel group was the best. The above results show that the self-healing hydrogel of the invention has a good therapeutic effect in the field of diabetic wounds infected with drug-resistant bacteria, and is expected to be clinically applied.

[0049] Comparative Example 1

[0050] The method for preparing graphene quantum dots comprises the following steps:

[0051] 250 mg of pyrene was added to a three-necked flask, and then 20 mL of HNO3 was added, and then it was refluxed and stirred at 80°C for 10 hours to nitrate it into trinitropyrene; after cooling to room temperature, the mixture was washed with deionized water and filtered through a 0.22 μm filter membrane to obtain an intermediate product; the obtained intermediate product was uniformly dispersed in a NaOH solution (75 mL, 0.2 M) by ultrasound to obtain a suspension; the suspension was transferred to a reactor and heated at 200°C for 10 hours; after the reaction was completed, it was cooled to room temperature, and the product was filtered through a 0.22 μm microporous membrane to remove insoluble products, and then dialyzed in a dialysis bag (1000 Da) for 48 hours to remove salts and unfused small molecules; after vacuum freeze-drying, purified GQDs without active carbonyl groups were obtained.

[0052] The infrared spectrum characterization results of the GQDs obtained in this comparative example are as follows Figure 6 .like Figure 6 As shown, FTIR spectrum analysis shows that at 3425cm -1The strong and considerable vibration at 1576cm -1 The strong vibration at 1850-1650 cm-1 is attributed to the C=C bond, and no carbonyl group vibration is observed at 1850-1650 cm-1. -1 This result proves that GQDs without active carbonyl groups were successfully prepared.

[0053] For further comparison experiments, according to the preparation scheme of the self-healing hydrogel in Example 2, the carbon dots containing active carbonyl groups were replaced with graphene quantum dots without active carbonyl groups. Under the same experimental conditions, the corresponding experimental operations were carried out. After the two were mixed for half an hour, the results were as follows: Figure 7 shown.

[0054] like Figure 7 , it can be seen that under the same reaction conditions, graphene quantum dots without active carbonyl groups cannot cross-link with amine-containing polymer compounds to form hydrogels.

[0055] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0056] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a self-healing hydrogel based on carbon dot cross-linking, characterized in that: The following steps are involved: In an aqueous solution system, carbon dots containing active carbonyl groups and organic polymer compounds containing amine groups are mixed and then subjected to cross-linking reaction to obtain a self-healing hydrogel.

2. The method for preparing the self-healing hydrogel based on carbon dot cross-linking construction according to claim 1, characterized in that: The reaction temperature is 25-55°C.

3. The method for preparing the self-healing hydrogel based on carbon dot cross-linking construction according to claim 1, characterized in that: In the aqueous solution, the concentration of carbon dots is 0.5-10 wt %; and the concentration of the organic polymer compound is 1-20 wt %.

4. The method for preparing the self-healing hydrogel based on carbon dot cross-linking construction according to claim 1, characterized in that: The mass ratio of the carbon dots to the organic polymer compound is (1:40)-(10:1).

5. The method for preparing the self-healing hydrogel based on carbon dot cross-linking construction according to claim 1, characterized in that: The organic polymer compound includes at least one of chitosan and its derivatives, chitosan oligosaccharides and their derivatives, polyacrylamide and its derivatives, gelatin and its derivatives, polyethyleneimine and its derivatives, polylysine and its derivatives, polyacrylamide and its derivatives, gelatin and its derivatives, polyethyleneimine and its derivatives, and silk fibroin and its derivatives.

6. The method for preparing the self-healing hydrogel based on carbon dot cross-linking construction according to claim 1, characterized in that: The method for preparing the carbon dots containing active carbonyl groups comprises the following steps: Slowly add an alkaline substance to a solution containing aldehyde compounds and / or ketone compounds, and stir the solution for reaction for more than 30 minutes at room temperature. After the reaction is completed, ultrasonically treat the obtained reaction product with dilute acid and water until solid precipitates, then separate the solid from the liquid, wash the solid with water until it is neutral, and dry it to obtain the carbon dots containing active carbonyl groups.

7. The method for preparing the self-healing hydrogel based on carbon dot cross-linking construction according to claim 6, characterized in that: The aldehyde compound is at least one of acetaldehyde, propionaldehyde, butyraldehyde, succinaldehyde, valeraldehyde, glutaraldehyde, hexanal, adipaldehyde, heptanal, octanal, nonanal, decanal, undecanal, dodecanal, tridecanal, tetradecanal, pentadecal, phenylacetaldehyde, and methylphenylacetaldehyde; and / or the ketone compound is at least one of acetone, 2-butanone, 2-pentanone, 3-pentanone, 2-hexanone, cyclohexanone, 2-heptanone, cycloheptanone, 2-octanone, cyclooctanone, 2-nonanone, decanone, undecanone, dodecanone, tridecanone, tetradecanone, pentadecane, acetophenone, and methylacetophenone; and / or the alkaline substance is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, carbonate, and carboxylate.

8. The method for preparing the self-healing hydrogel based on carbon dot cross-linking construction according to claim 6 or 7, characterized in that: The method also includes the step of adding a doping element source into the aldehyde-containing compound and / or ketone-containing compound.

9. The self-healing hydrogel obtained by the preparation method according to any one of claims 1 to 8.

10. The self-healing hydrogel according to claim 9 is used in the fields of tissue engineering, regenerative medicine and cosmetics.